The Nun in the Synagogue : Judeocentric Catholicism in Israel - Polyakov, Emma O'Donnell (Book collections on Project MUSE., 2020)
"A study of Catholic perceptions of Jews, Judaism, and Israel, offering an exploration of biographical narratives and reflections on Holocaust trauma, conversion, Zionism, and religious identity"--